Formação continuada entre professores/as de educação física escolar na cidade de Caravelas - Bahia: uma perspectiva para novos olhares sobre as práticas pedagógicas - Ferreira, Luiz Leonardo Soares (2023)
This study has the general objective of structuring an experimental process of collaborative continuing education among FE teachers from public schools, from Elementary School II, in the city of Caravelas, Bahia. Specifically, we sought to: a) carry out a survey of pedagogical practices in PE classes in Elementary II in public schools in the municipality; b) design and develop with the teachers an experimental proposal for continuing education based on the critical perspectives of school FE; c) Analyze possible influences of continuing education on teachers' pedagogical practices; d) sensitize the executive power of Caravelas/BA on the importance of the need for specific continuing education for PE teachers through the creation and publication of a blog with reports of experiences and content related to the practices experienced. The research was methodologically based on the principles of participant research. All the data produced by the research actors start from a process of constant interaction between peers, with a view to reflecting on their pedagogical practices and the possible influences of training on these reflections. The analysis was based on studies by authors such as Huberman (2000), which brings us possible influences from the professional life cycle of teachers; Zeichener (1998, 2008) and Schön (1992), who discuss training based on a pedagogical praxis based on the process of action-reflection-action; Candau (1996) who contributes to discussions about the school as a locus of continuing education and the enhancement of teaching knowledge and; Figueiredo (2004) who considers the influences of socio-corporal experiences on the way teachers act. The conclusive perceptions indicate that continuing education, with a view to stimulating reflection on pedagogical practices in a collaborative way, is a possible way of working in the context presented in the municipality. It points out that the management policy of the Secretariat of Education and Sports of Caravelas/BA, as a determining factor in limiting the possibilities of articulation of the teaching collective. Finally, it brings physical education teachers collaboratively closer to research in an attempt to encourage involvement and complicity as protagonists of continuing education.